Analysis of Casemix Team Performance in the Successful Verification of National Health Insurance Claims at Hospital X - Andani, Luluk; Jati, Sutopo Patria; Agushybana, Farid (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Casemix team is a vital component of the hospital healthcare system, focused on providing patient care. The Casemix team comprises coding, posting, clinical pathway, and information technology components. Hospital management considers the performance of the Casemix Team to be suboptimal. Objective: This study aimed to ascertain the factors contributing to the suboptimal performance of the Casemix team. Method: The research method employed in this study was qualitative research, specifically utilising a case study approach. The data were gathered by observing the claims management conducted by the Casemix Team and conducting in-depth interviews with key individuals, including the Casemix Team, the President Director, the Finance Manager, and the BPJS (Social Security Agency on Health) verifier. The data collection in this study followed a cross-sectional design. The data was collected through observation of claim management by the Casemix Team and in-depth interviews with the informans. The data processing and analysis used the content analysis method, which involves data collection, data reduction, data presentation, and drawing conclusions from the results. Results: The suboptimal performance of the Casemix Team can be attributed to several factors. Firstly, the team's knowledge regarding posting and the clinical pathway was inadequate. Secondly, the completeness of the claim- supporting files was lacking. Thirdly, there was a lack of special compensation. Fourthly, the supervision provided by the leadership was not optimal. Lastly, the team faced constraints due to internet connection issues. Conclusion: Casemix Team Performance Indicators are seen in terms of quality, quantity, timeliness, effectiveness, and independence.